1988
DOI: 10.1364/ao.27.001050
|View full text |Cite
|
Sign up to set email alerts
|

Rod densitometry in congenital stationary night blindness

Abstract: Rod densities were measured in ten patients with congenital stationary night blindness (CSNB) using the Utrecht densitometer. In five patients rod density was within the range observed in a group of control subjects. One of these patients reached a normal rod two-way density after a prolonged regeneration time. In five patients with different hereditary patterns of CSNB we found decreased amounts of rhodopsin. These observations deviate from the findings on four CSNB patients hitherto described in the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This should result in a large decrease in INL sensitivity (an increase in a P2 ) for CSNB patients (see references in Hood & Greenstein, 1990). More recently, it has been shown that some CSNB patients have reduced rod pigment content as well (Keunen et al, 1988). This would produce a decrease in receptor sensitivity (an increase in ff P3 ) for these patients.…”
Section: Fitting the Model To B-wave Data From The Patientsmentioning
confidence: 99%
“…This should result in a large decrease in INL sensitivity (an increase in a P2 ) for CSNB patients (see references in Hood & Greenstein, 1990). More recently, it has been shown that some CSNB patients have reduced rod pigment content as well (Keunen et al, 1988). This would produce a decrease in receptor sensitivity (an increase in ff P3 ) for these patients.…”
Section: Fitting the Model To B-wave Data From The Patientsmentioning
confidence: 99%
“…Dark adaptation curves with similar diphasic appearance in night-blind individuals are presented, among others, by Keunen et al (1988). These cases, indeed, were presumed to be autosomal recessive types and incomplete types of CSNB.…”
mentioning
confidence: 60%
“…In incomplete CSNB (Miyake et al 1986) the electrical cone characteristics are depressed, especially in the dark adapted state (Miyake et al 1987). Dark adaptation curves with similar diphasic appearance in night-blind individuals are presented, among others, by Keunen et al (1988). These cases, indeed, were presumed to be autosomal recessive types and incomplete types of CSNB.…”
mentioning
confidence: 60%
See 2 more Smart Citations